Piratica : being a daring tale of a singular girl's adventure upon the high seas - Lee, Tanith (Dutton Children's Books, 2004)
Artemesia finally escapes the prim and proper world of finishing schools and sets out to win her mother's title as pirate queen of the seas until she meets her match against Goldie Girl, the treacherous captain of the pirate ship "Enemy."